CHILD VIOLENCE AGAINST PARENTS: PSYCHOLOGICAL AND PEDAGOGICAL ASPECTS AND PROBLEMS OF LEGAL REGULATIONS OF LIABILITY - Vanaga, Sanita; Pumpuriņa, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Domestic violence is a cycle of various harassment in which the abuser can be any member of the family. Both media and research on domestic violence focus on the behaviour of adult family members, while there is a lack of research analysing child abuse, for example against their parents. The current legal framework establishes the procedure for bringing an abusive person to justice, however, the provided sanctions do not apply to a child being violent in case the offense is not of a criminal nature. The study presents the research in two parts, the first part, indicating the psychological and pedagogical aspects of the problem, and the second - the problem of the legal regulation of liability.The aim of the study was to analyse the regulatory framework, which determines the child's responsibility in cases of child-to-parent violence, to identify the problems of the legal framework and to develop proposals for the improvement of the legal framework.The study was developed interdisciplinary, performing the analysis of national and international legal acts, analysing statistical data and research on current issues. Analytical and descriptive method, grammatical, historical, teleological and systemic interpretation methods were used in the study.As a result of the research, a number of problems were identified. These were related to the identification of a child being violent, the rights and responsibilities of the family and society in cases of escalating violence, as well as the issue of taking responsibility for the child's violence. At the same time, it was concluded that cases of violence by children to parents are difficult to identify, which may be due to the parent-child relationship and ignorance of the parent's problem, resulting in a formal determination of the child's responsibility in case of violence. In turn, the legal framework should strengthen not only the procedure of holding the children responsible for their violent behavior, but also to call for interdisciplinary prevention of violence committed by children.